The Impact of Servant Leadership Style and Work Discipline on Employee Performance at An-Nuqthah Foundation, Tangerang City - Nisa, Siti Raudhotun (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the influence of Leadership Style and Work Discipline on Employee Performance at the An-Nuqthah Foundation in Tangerang City, both partially and simultaneously. The method used is quantitative with saturated sample technique, involving 75 respondents. Data analysis includes validity, reliability, classical assumptions, linear regression, correlation coefficient, determination coefficient, and hypothesis testing (t-test and f-test). The results of the study indicate that simultaneously, Leadership Style and Work Discipline have a significant effect on employee performance with the regression equation Y = 8.476 + 0.167 X1 + 0.572 X2 + e. The correlation coefficient of 0.696 indicates a strong relationship, while the determination coefficient (Adjusted R²) of 47.0% indicates the contribution of both variables to performance, while 53.0% is influenced by other factors. Hypothesis testing shows F count (33.798) > F table (3.12) and sig (0.000) < 0.05, so Ho is rejected and Ha is accepted, which means there is a significant influence between Leadership Style and Work Discipline on employee performance.